Fabrication of a laccase-immobilised biosensor based on carboxylated multi-walled carbon nanotubes for sensitive tyramine detection - Nurul Syazwani Kizzon; Syaza Azhari; Nurul Hana Mas’od; Nadrahtul Huda Misral (Penerbit Universiti Kebangsaan Malaysia, 2025)
Tyramine is a molecular substance found in foods that can adversely affect consumers due to its toxicity, posing risks to both human health and food quality. Therefore, it is crucial to monitor the excessive concentration of tyramine in meals. Biosensors have attracted considerable attention from researchers due to their benefits, including portability, ease of use, and high specificity. This study aimed to develop a biosensor by specifically modifying multi-walled carbon nanotubes (MWCNTs) with a carboxyl group (-COOH) to immobilise laccase (Lac) enzyme molecules, thereby enhancing the biosensor’s characteristics, including faster response times, a wider detection range, and higher sensitivity. The modified screen-printed carbon electrode (SPCE) was characterised using differential pulse voltammetry (DPV), Field Emission Scanning Electron Microscopy (FESEM), and Fourier Transform Infrared Spectroscopy (FTIR). The optimised parameters of the Lac-MWCNT-COOH SPCE biosensor exhibited excellent performance at pH 7 in phosphate buffer solution, within the tested pH range of 5.0-9.0, with 3 µL of laccase enzyme (range 1-5 µL), at 0.2 V deposition potential (range 0.1-0.5 V), and a deposition time of 5 s (range 3-7 s). The SPCE modified was successfully fabricated for tyramine determination, achieving a limit of detection (LOD) of 0.09 mM.